(untitled) (Advances in Applied Mathematics and Mechanics, 2013)
In the present work, both computational and experimental methods are employed to study the two-phase flow occurring in a model pump sump. The two-fluid model of the two-phase flow has been applied to the simulation of the three-dimensional cavitating flow. The governing equations of the two-phase cavitating flow are derived from the kinetic theory based on the Boltzmann equation. The isotropic RNG k-ε-k_ca turbulence model of two-phase flows in the form of cavity number instead of the form of cavity phase volume fraction is developed. The RNG k-ε-k_ca turbulence model, that is the RNG k-ε turbulence model for the liquid phase combined with the k_ca model for the cavity phase, is employed to close the governing turbulent equations of the two-phase flow. The computation of the cavitating flow through a model pump sump has been carried out with this model in three-dimensional spaces. The calculated results have been compared with the data of the PIV experiment. Good qualitative agreement has been achieved which exhibits the reliability of the numerical simulation model.